Global Trends of Segmental Phonemes Assessment in EFL: A Systematic Literature Review - Karimah, Syahadah Albaqiyatul (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to identify and analyze global trends in segmental phonemes assessment within the context of English as a Foreign Language (EFL) through a Systematic Literature Review (SLR) guided by the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Initial data were retrieved from the Scopus and Google Scholar databases using the Publish or Perish software, yielding a total of 534 articles with relevant keywords. The screening process followed the four main PRISMA stages resulting in 20 articles that met all inclusion criteria: a focus on segmental phonemes assessment, publication between 2019–2025, and the presence of a clear research methodology. The analysis revealed that approaches to evaluating segmental pronunciation in EFL are grounded in three key theoretical pillars: intelligibility theory, phonological awareness, and technological integration in language learning. The dominant trend observed is the adoption of advanced technologies such as Automatic Speech Recognition (ASR), Computer-Assisted Pronunciation Training (CAPT), and AI-based platforms with real-time feedback, all of which have been proven to enhance pronunciation accuracy. Additionally, the findings highlight the importance of pedagogical and technical training for instructors and the limited research on teacher evaluation and cross-cultural influences. These insights provide a foundation for developing adaptive, technology-driven, and socially responsive pronunciation assessment systems that address the needs of diverse global learners in contemporary EFL education.